When Servant Becomes Leader: The Corazon C. Aquino Success Story as a Beacon for Business Leaders - Udani, Zenon Arthur S.; Lorenzo-Molo, Caterina F. (2013)
This article makes the case for servant leadership as a model for business in its analysis of the leadership style of former Philippine president, Corazon C. Aquino. Premised on the idea that self-management requires deep spirituality lived integrally (and sustained by an interior or inner life), we identify specific traits and virtues of Aquino and their implications on her leadership and effect on people. The article begins with an introduction to establish the contribution of servant leadership on business. It continues with a summary of key points in servant leadership literature. Then, we analyze Aquino as a person and leader and find that the former spilled over to the latter. We conclude by providing a model based on Aquino’s journey into the role of servant leader; thus, presenting a framework that charts the path toward servant leadership to help businesses address the leadership crisis brought on by an Enron-WorldCom-Tyco dominated business culture.
Keywords: Corazon Aquino; Philippines; Virtue; Servant leader